The effects of adolescent social isolation and group housing on adolescent binge drinking in mice - Jyoti Lodha; Alanna Morgan; Rithika Balguri; Vera Purcell; Jennifer T. Wolstenholme (PLoS ONE, 2026)
Adolescence is a developmental period characterized by behavioral changes such as sensation seeking, impulsivity, and diminished self-control to inhibit behaviors, which can lead to increased risky behavior, including the initiation of binge drinking. Due to the necessity of peer-peer social interactions for proper development, social isolation can be particularly disruptive at this time, altering proper neural development and function and increasing risk for alcohol misuse. To investigate the effects of social context on ethanol drinking, we modulated the social environment of a mouse using single housing, neighbor cages, or group housing and evaluated ethanol drinking behavior in the intermittent 2-bottle choice and drinking in the dark models. Using neighbor cages versus social isolation, ethanol intake was largely unaffected by housing condition from adolescence into early adulthood. However, single housing increased adolescent ethanol intake using a drinking in the dark model in both sexes. Group housed mice with concurrent ethanol access drank significantly less than isolated animals. Manipulating the number of ethanol bottles per cage increased the volume of ethanol consumed, but did not affect the relative differences in intake between group and single housed mice. Adolescent binge drinking increased adult intake only in group housed mice. In sum, social isolation during adolescence increased ethanol intake while drinking with conspecifics decreased ethanol intake. Drinking in isolation tended to increase ethanol intake, suggesting the presence of a conspecific alters the motivation to drink ethanol.